DMK: Rebranding a footwear brand to connect with millennials and Gen Z - LUI, Patricia (Institutional Knowledge at Singapore Management University, 2023)
This case study begins in October 2022, two years after Sophia and Eileen Goh, who were sisters, rebranded the footwear company to expand its customer base from baby boomers and Gen X to millennials and Gen Z. The footwear brand was originally positioned as a workwear brand, specifically to cater to women who had wide feet and suffered from bunions. Growth was steady in the first 20 years and was primarily driven by word-of-mouth. However, by 2020, the brand had lost its appeal to the millennials and Gen Z. In September 2020, the sisters embarked on an initial rebranding strategy by repositioning DMK as shoes for every occasion and milestone across a woman’s lifetime journey. The rebranding effort was further strengthened by focusing on five pillars including supporting the female community, product diversification, reintroduction of DMK Care to enhance comfort of the shoes, introducing a new retail experience to provide immersive customer experience at the outlets and strengthening of DMK’s digital capabilities. The Singapore footwear market was worth US$870 million in 2020 and was expected to grow to US$1,270 million by 2025. What else could DMK do to further elevate the brand and future prooffuture-proof the business? The learning objectives of the case include: • Use the SWOT and TOWS matrices for developing rebranding strategies • Apply concepts of rebranding (e.g., Customer-Based Brand Equity model, Servicescape model) to revitalise a brand • Use the influencer marketing strategy to strengthen the revitalised brand position in the digital age